Institutional, Technology, and Policies of End-of-Life Vehicle Recycling Industry and Its Indication on the Circular Economy- Comparative Analysis Between China and Japan - Wang, Jia; Sun, Lu; Fujii, Minoru; Li, Yuke; Huang, Yonghe; Murakami, Shinsuke; Daigo, Ichiro; Pan, Wei; Li, Zhenbiao (Frontiers in Sustainability, 2021)
With economic development and accelerated industrialisation, resource consumption has seen rapid increase. Against such a consumer boom, vehicle ownership has rocketed up, which also brings surging numbers of end-of-life vehicles (ELVs). Thus recycling and disposing those ELVs turn out to be a head-scratching issue. In China, over the past two decades, the Chinese vehicle ownership had grown rapidly to 261.5 million in 2019. Likewise, the ELV recycling industry in China also faces mounting challenges, especially in policy-making, recycling system, and the remanufacturing industry. In recent years, despite the emergency of a group of large-scale quality dismantling enterprises, the overall technological level in the industry and the recycling rate require further advancement. In contrast, countries with highly mature automobile industry have seen a different image. Japan, for instance, has been the pioneer in the field of ELV recycling, created well-rounded laws and regulations on the industry, and developed advanced know-hows to cope with technical challenges. Therefore, this study, firstly, tries to summarize the laws and regulations and the latest industrial status of ELVs recycling in China and Japan. The deviation, if any, shall be analysed between Japan‘s existing system and policy design, and the possible causes. Secondly, the Material Flow Analysis (MFA) method is adopted to analyse the changes of Resource Input Intensity (RII) of steel and oil for vehicles over the past 10 years, which shall provide the basis for future research on material recycling and waste treatment. Thirdly, the overall recycling rate of China’s automobile products is analysed, with the prediction that as technologies advance and related policies evolve, the recycling rate shall increase from 90% to 98% within five years. Fourthly, against the backdrop of circular economy development, this paper tries to provide an enlightenment to ELVs recycling management in China and Asian countries, with the stage of social development, policy system, social awareness of resource recycling, market guidance and other factors combined in the research. As a whole, this study tries to facilitate the sustainable development of the ELV recycling industry, provides support for the policy-making, and contributes to the building of a resource-saving and recycling-oriented society.